Participación de las entidades promotoras de salud (EPS) en el mercado del aseguramiento de salud, Colombia, 1995-1998 (1999)
ABSTRACT: The Law 100 of 1993 defined a legal framework seeking to consolidate a health insurance system based on market. In that context, the “Entidades Promotoras de Salud” (EPS) play the role of affiliating and receive, by assignment, the quotation of those who should affiliate to the Contributive Regime, as well as to manage fund destined to ensure poorer people to the Subsided Regime. In this article, the participation of the individual EPS in the health insurances system during the 1995-1998 periods is analyzed. The basic information was taken from a research carried out by teacher of the National Faculty of Public Health (University of Antioquia) and directed by the author. Both Regimes were analyzed separately. It is concluded that private EPS tend to gain higher participation in the health insurance market, while the public ones face serious problems and are loosing importance.